The Impact of using WhatsApp® Groups on the Palestinian University Students' Productive Skills Improvement - عمر, ملاك ناظم عبد المطلب (An-Najah National University, 2021)
This study aims to explore the extent of using WhatsApp and its impact on writing and speaking skills of the university students who are studying English (101) as a compulsory course at An-Najah National University during the academic year 2020/2021. The sample consists of (60) students who study English (101) as a compulsory requirement during the first semester of the academic year 2020/2021. Students were divided into two groups: the control group contains 30 students who were taught in the traditional way, while the experimental group contains 30 students who were taught in a blend mode of teaching that combines both using WhatsApp method and the conventional way of teaching. Results indicated that WhatsApp groups have improved students’ speaking skill by 31.5%. Furthermore, the experimental group results show a difference in the mean score of writing skill test between pre-tests and post-tests; the results indicate that there is an apparent difference in favour of the post-test results for the experimental group. The results indicate the WhatsApp groups have improved students writing skill by 43.2%. Based on the results of the study, the researcher recommends the following: 1- Students should work seriously on getting benefits from the application that they spend most of their time on, so they have initiate groups or to join different learning groups on WhatsApp, Facebook or Instagram with their friends and using it for developing their English language. 2- Teachers should use WhatsApp groups for improving students’ four skills not just their productive skills, by training their students on how to use WhatsApp for educational purposes not just as a social media.
أثر استخدام مجموعات الواتس اب على تطور المهارات الإنتاجية لدى طلبة الجامعات الفلسطينية